Fine needle aspiration: a simple and handy tool to diagnose malignant lymphadenopathy - P., Sravani; M., Neeraja; C., Bhavani (International Journal of Research in Medical Sciences, 2017)
Background: Fine needle aspiration cytology (FNAC) of the lymph node is a simple useful screening test to diagnose suspected and unsuspected secondary and primary lymph node malignancy. The aim of the present study is to know the role of FNAC in the diagnosis of clinically suspected and unsuspected lymph node malignancies. Study design: prospective cohort study. Methods: Study material comprise of ‘76’ lymph nodes aspirates reported as malignant on cytology, out of total 445 cases of lymph node aspiration in two years period i.e. from October 2014 to September 2016.These 76 smears were studied and tabulated according to their cytomorphology and the lymph node group affected was noted. The clinical and radiological data were also noted. Results: Males were found more affected than females. cervical lymph node is the commonest group involved. Metastasis from squamous cell carcinoma was the most common diagnosis made on cytology. Conclusions: FNAC is found simple and very useful tool for diagnosing malignant lesions of lymph nodes especially in case of metastasis.